Fostering a chemistry safety culture despite limited resources: A successful example from academic research laboratories in Argentina - Fracaroli, Alejandro Matías (2021)
Scientists understand that no result is more important than the welfare of the investigators and the people around them. Safety culture is an integral part of industrial and academic jobs; however, safety training has only recently been added to chemistry classroom and laboratories. Chemistry laboratories expose workers to a variety of hazards, and implementing safety programs and regulations requires both changes and investment to improve the culture of safety. However, scientific research in developing countries frequently involves using creative alternatives to overcome obstacles related to limited financial resources. Therefore, we developed a 12 steps strategy termed Safety Watch, to foster chemistry safety culture in research laboratories without substantial financial resources. A significant milestone in this strategy was a Hygiene and Safety Internal Advising Committee (H&SIAC) composed of self-motivated researchers and students who allocated part of their time to detect, develop, and implement low-cost solutions to reduce or eliminate safety hazards. After almost 15 years, this safety watch has led to sustainable growth in the personnel safety culture, and concomitantly, promoted institutional support and attracted the necessary investment. We believe this bottom-up approach, where the safety culture is improved first by the laboratory workers, making the necessary investment easier to obtain later, is a model that can be applied to other research laboratories with similar work environments.